(untitled) (Physical Education, Health and Social Sciences, 2025)
Introduction: Mental health awareness is crucial for nursing students, as they play a vital role in patient care. This study explores their attitudes, perceptions, and willingness to engage in mental health education and care, highlighting factors influencing their perspectives and the need for improved awareness. Methodology: This cross-sectional descriptive study was conducted at a nursing institute in Karachi, Pakistan, with a sample of 132 undergraduate nursing students selected through stratified random sampling. A validated self-administered questionnaire assessed demographic details, mental health awareness, attitudes, and help-seeking behaviors. Data were analyzed using SPSS, employing descriptive and inferential statistics, ensuring ethical considerations. Result: Among 132 nursing students, 68% had prior exposure to mental health topics, but only 40% had a strong understanding. Stigma was prevalent, with 45% holding negative perceptions. Only 30% showed strong willingness to pursue mental health nursing. Barriers to seeking help included fear of judgment (60%) and lack of trust (50%). Conclusion: The study found that nursing students had moderate mental health awareness but exhibited stigma and reluctance toward psychiatric nursing. Limited exposure and societal perceptions influenced their attitudes. Integrating mental health education into curricula and awareness campaigns is essential to reduce stigma, improve confidence, and enhance students’ ability to support mental health care effectively.